Liposarcome du cordon spermatique - Kostka, Rodomil; Baitler, Tomas; Zachoval, Roman; Sosna, Bohuslav; Palascak, Paul (Progrès en urologie. Formation médicale continue, 2006)
Liposarcoma of the spermatic cord is rare. It usually presents as a painless slowly-growing scrotal mass of consistency like lipoma. Inguinal orchiectomy is an adequate surgical approach. Retroperitoneal lymphadenectomy is not indicated owing to the low malignancy potential of the sarcomas. Value of adjuvant radiotherapy/chemotherapy remains uncertain. Recurrences are frequent, owing to incomplete surgical removal of the tumor. We report on a 62 year old male who presented with a half a year history of a soft painless mass in the left scrotum extending from the groin up to the testis. Clinical examination suggested inguinal hernia. Radical orchiectomy was performed. Histological examination revealed a well-differentiated liposarcoma of sclerosing subtype. No evidence of recurrence or metastases has been noted during the 6-month and one year follow-up without any postoperative adjuvant therapy.
Keywords: Liposarcoma; Middle Aged; semenný provazec; liposarkom; lidé středního věku; nádory mužských pohlavních orgánů; Humans; Spermatic Cord; mužské pohlaví; Genital Neoplasms, Male; lidé; Male